Myśl Jana Pawła II jako odpowiedź na pytania filozoficzne medycyny = John Paul II`s reflections as the answer to philosophical questions posed by medicine - Jaranowski, Paweł (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents selected elements of John Paul II`s teaching concerning philosophical aspects in medicine, with particular interest in their impact on general culture. It considers John Paul II`s assessment of issues fundamental for solving ethical dilemmas in medicine: human life normativity, criteria of humanity, the idea of person, teleology of medicine. Further, it offers an insight into papal judgement of medical experiments on humans and transplantion.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; nauczanie; filozofia medycyny